Cross-cultural Adaptation and Psychometric Properties of the Arabic Version of the Academic Nurse Self-Efficacy Scale - Junel Bryan Arre Bajet; Jonas Preposi Cruz; Ejercito Mangawa Balay-odao; Jennifer Mesde; Nahed Alquwez; Khalaf Alotaibi; Sheerween Cacanando (Makara Journal of Health Research, 2023)
Background: Students’ academic self-efficacy is greatly associated with their academic performance. An effective instrument is needed to assess academic self-efficacy in the Saudi context. This study assessed the psychometric properties of the Academic Nurse Self-Efficacy Scale-Arabic version (ANSE-A) given to student nurses and the associations between the students’ demographics and overall ANSE-A scores.